2014
DOI: 10.1038/cmi.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Platelets promote allergic asthma through the expression of CD154

Abstract: Platelet activation is associated with multiple immune responses and the pathogenesis of various immune-related diseases. However, the exact role and the underlying mechanism of platelets in the progression of allergic asthma remain largely unclear. In this study, we demonstrate that during antigen sensitization, platelets can be activated by ovalbumin (OVA) aerosol via the upregulation of CD154 (CD40L) expression. Platelet transfer promoted allergic asthma progression by inducing more severe leukocyte infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
1
31
2
Order By: Relevance
“…Specifically, platelet depletion has been shown to reduce the allergen-induced infiltration of eosinophils, lymphocytes, monocytes/macrophages, and neutrophils into the lungs of rodents. 27,[36][37][38] In this regard circulating platelet-leukocyte complexes occur at far greater frequency after both spontaneous asthma attacks in a biphasic manner or after allergen challenge in the clinic (Fig 2). 13,17,37 The possible significance of these platelet-leukocyte complexes is presumably to act as a ''priming'' step to promote efficient leukocyte adhesion to the vascular endothelium because leukocytes attached to platelets display more of the aM subunit (CD11b) of the aMb2 integrin macrophage 1 antigen (CD11b/CD18) than circulating leukocytes not attached to platelets.…”
Section: Pulmonary Leukocyte Recruitment Is Platelet Dependentmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, platelet depletion has been shown to reduce the allergen-induced infiltration of eosinophils, lymphocytes, monocytes/macrophages, and neutrophils into the lungs of rodents. 27,[36][37][38] In this regard circulating platelet-leukocyte complexes occur at far greater frequency after both spontaneous asthma attacks in a biphasic manner or after allergen challenge in the clinic (Fig 2). 13,17,37 The possible significance of these platelet-leukocyte complexes is presumably to act as a ''priming'' step to promote efficient leukocyte adhesion to the vascular endothelium because leukocytes attached to platelets display more of the aM subunit (CD11b) of the aMb2 integrin macrophage 1 antigen (CD11b/CD18) than circulating leukocytes not attached to platelets.…”
Section: Pulmonary Leukocyte Recruitment Is Platelet Dependentmentioning
confidence: 97%
“…Therefore it is of considerable interest that a number of studies have reported that platelet depletion can reduce allergen-induced bronchoconstriction and allergen-induced BHR. 27,36 However, the precise mechanism or mechanisms of this platelet-dependent BHR are not fully understood.…”
Section: Platelets and Bhrmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] CD154 release has been shown to activate platelets during allergen sensitization in asthma, stimulating other white blood cells to cause inflammation to become more pronounced. [31] In the literature, we could not find a study investigating the relationship between asthma attacks and platelet count and PLR. In our study, the platelets were not associated with frequent emergency admissions, whereas high PLR values were associated with severe episodes requiring hospitalization.…”
Section: Resultsmentioning
confidence: 97%
“…Levels of coagulation parameters, platelets, fibrinogen, tissue factor, thromboxane A2, thrombin and activated protein C may reflect thrombosis formation during the pathophysiological process of asthma (5,6). Platelets activated by the up-regulation of cluster of differentiation 154 may release the platelet δ, α and λ granules, induce pulmonary inflammation and enhance the T helper cell 2 immune response, thus aggravating asthma severity (7). The extracellular signal-regulated kinase 1/2 signaling pathway serves an important role in the process of thrombus-promoting airway remodeling in ovalbumin allergic rats (8).…”
Section: Introductionmentioning
confidence: 99%